TECHNOLOGICAL INNOVATION IN ACCOUNTING AUDIT: IMPLICATIONS FOR AUDIT EFFICIENCY AND EFFECTIVENESS - Edi, Sarwo; Husna, Asmaul; Hanum, Fauziah; Saputra, Julfan (Proceeding International Seminar of Islamic Studies, 2024)
In the era of digital transformation, technological innovation has become a driving force in advancing accounting practices, especially in the context of audit examinations. This paper investigates the impact and implications of using the latest technology in accounting audits, with a focus on increasing audit efficiency and effectiveness. This research shows that the integration of technologies, such as big data analytics, artificial intelligence, and blockchain technology, can result in a significant transformation in the way auditors manage, analyze, and verify financial data. The success of technology in improving the quality of audit services is also related to professional ethical challenges that arise along with the development of this technology. The results of this research provide in-depth insight into how technological innovation can have a positive impact on accounting audits, forming the basis for more adaptive and efficient audit practices.